Validating hybrid training curriculum for primary science teachers: Ubon Ratchathani Geopark study - Chanarak Vetsawat; Natthitaporn Chatree; Piyaphat Nithitakkharanon (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
Science education is essential for helping young students develop science literacy. The study used geopark as a learning resource to get students excited about science. This study develops and validates a training curriculum for primary science teachers by employing the geology course, Ubon Ratchathani Geopark. The findings revealed that the program consisted of 4 modules and it has potential for use in the fields of science education and ecotourism. Students of both Thai and English may benefit emphasizing on scientific communication through junior guides' practices. In this course, teachers can create learning management systems by utilizing geopark resources as real-world media and develop virtual representations. Consequently, the Ubon Ratchathani Geopark serves as the primary location for the integration of information for students who have gained their knowledge through hands-on and mind-on experiences in a natural classroom.